Antifungal Activity of Apple Cider Vinegar on Candida Species Involved in Denture Stomatitis. Issue 4 (14th September 2014) - Mota, Ana Carolina Loureiro Gama; de Castro, Ricardo Dias; de Araújo Oliveira, Julyana; de Oliveira Lima, Edeltrudes
Abstract Purpose To evaluate the in vitro antifungal activity of apple cider vinegar on Candida spp. involved in denture stomatitis. Material and Methods The microdilution technique was used to determine the minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) of apple cider vinegar containing 4% maleic acid, and nystatin (control). Further tests of microbial kinetics and inhibition of adherence to acrylic resin were performed testing different concentrations (MIC, MICx2, MICx4) of the products at time intervals of 0, 30, 60, 120 and 180 minutes. A roughness meter was used to measure the changes in surface roughness; color change of the acrylic resin specimens exposed to the test products in different concentrations and time intervals were also evaluated. Results Apple cider vinegar (4%) showed MIC of 2500 μg/ml and MFC of 2500, 5000, and 10, 000 μg/ml depending on the strain tested. Nystatin showed MIC of 3.125 μg/ml and strain‐dependent MFC values ranging from 3.125 to 12.5 μg/ml. The microbial kinetic assay showed a statistical difference between apple cider vinegar and nystatin (p < 0.0001). After 30 minutes of exposure, apple cider vinegar showed fungicidal effect at MICx4, whereas nystatin maintained its fungistatic effect. Apple cider vinegar showed greater inhibition of adherence (p < 0.001) compared to control. Apple cider vinegar did not significantly alter the surface roughness of the acrylic resin specimens compared to nystatin (p > 0.05), and both had no influence on their color. Conclusion Apple cider vinegar showed antifungal properties against Candida spp., thus representing a possible therapeutic alternative for patients with denture stomatitis.